Quanto custa um sonho?: a busca das mulheres pela maternidade e suas relações de consumo com a indústria reprodutiva - Santos, Isabela Racz (2022)
This research aims to understand how consumption integrates motherhood practices among women who seek to become pregnant through assisted reproduction (AR) techniques. From the perspective of Theories of Practice, our specific objectives are to assess how women who participate in the journey of consuming AR services experience and re-signify marketing aspects of the process and to understand what are the decisive factors for their consumption of AR services. About the methodology, 12 semi-structured interviews were carried out with women aged 33 to 44 years old who have already consumed or are interested in consuming AR services in order to have a biological child. They call themselves seekers. In all, 10:52:11 and 84.526 words of audiovisual content were recorded on the Google Meet platform, where all the interviews were carried out. The data were analyzed based on the French Discourse Analysis, mainly with the work of Orlandi (2009). As a result, we list that, by mobilizing the idea of empowerment and emancipation from the biological determination of female bodies, such as infertility, the AR market and the seekers themselves appropriate the neoliberal logic that blames them for the failure or success of treatments. Entrepreneurs of their bodies, women become responsible for their own surveillance and performance in a search for improvement to repair what nature was not able to provide alone. The discourse also reveal the women´s expectation of receive more information about the process and obtain more individualized and welcoming services from specialized doctors.